Structural analysis of the Azmir – Goizha anticline, north and northeast of Sulaimani city, Kurdistan Region, Northeast Iraq - Karim, Kamal Haji; Ahmad, Sirwan Hama (Sulaimani Journal for Pure and Applied Sciences, 2014)
The Azmir–Goizha anticline (AGA) is located directly to north and northeast boundary of Sulaimani city, Kurdistan Region, NE Iraq. The anticline originally consists of two main connected anticlines (Azmir and Goizha anticlines) with many smaller anticlines along southwest and northeast limbs. In the studied area, it has length and width of about (10 and 4) kms, respectively, with height of 1600 m (a.s.l). It extends from Weladar village, from southeast to Khamza village at the northwest and further extends outside of the studied area. The anticline has very complicate structural setting and recently few structural analyses were conducted by different workers. The present study is an attempt to discover the actual structural setting of the anticline and try to review the previous studies critically by using data collected in the field with aid of precise stratigraphic analysis. Structurally, the previous pigy-back thrust imbricated fan is changed to nearly isoclinal detachment fold, which is detached in the form of either lift-off detachment fold or multi- detachment fold or multi-detachment faulted fold. In the core of the anticline, the accommodation of the shortening is preserved as second-order folding or second-order conjugate faulting. The competent cover (outer layers) of the anticline consists of Kometan and upper part Balambo formations. Core Azmir and Qaywan anticlines are occupied plastic incompetent layers of Sarmord Formation and lower part of Balambo formations while that of Azmir Bichkola and Naugirdan (or Goizha) anticlines are occupied. These units are deformed as disharmonic buckle folds in the cores. The main detachment had occurred in the lower part of the Sarmord Formation (Lower Cretaceous) and inside Jurassic rocks. All the mapped strike-slip and reverse faults, in the previous studies are not recorded in the present study. Furthermore, this study recommends excluding the anticline from the Imbricate Zone and including it within the High Folded Zone.
Keywords: Azmir anticline; Goizha anricline; Structural analysis; Sarmord Formation; BalamboFormation; Kometan Formation; Gulneri Formation; Dokan Formation